The development of teaching materials based on problem solving exploration with microsoft kaizala applications - Sari, Nenden Mutiara; Setiani, Ana; Rinangkit, Ina; Munawar, Hanhan Subhan (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
The effectiveness of implementing online learning during the COVID-19 pandemic has not been satisfactory in terms of problem-solving abilities. The presentation of teaching materials presented in the online platforms used has not been able to identify the extent of student understanding in problem-solving exploration. Therefore, this research aims to produce Kaizala teaching materials based on problem-solving exploration. The ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model was used in this research to produce these teaching materials. The subjects of this research trial were grade VIII junior high school students in a public school in Ogan Komering Ulu Regency, Palembang. The choice of the place for this research was based on the fact that the mathematics learning carried out at the school was by utilizing social media platforms. The instruments used in this research consisted of validation sheets of material, language, presentation, and problem-solving integration, a questionnaire on the practicality of teaching materials, and a problem-solving ability test to assess the effectiveness of the developed teaching materials. The results showed that: (1) the developed teaching materials were in the valid criteria; (2) the practicality of the developed teaching materials are at very high and high criteria; (3) The developed teaching materials also meet the criteria of effectiveness, whereas many as 82 percent of the test subjects obtained a score of not less than 75 and the effect size value belongs to the large category. Thus, it can be concluded that the developed teaching materials are suitable for supporting and facilitating students in problem-solving exploration activities.